Navigating around the DRC’s statistical potholes: New estimates on welfare and poverty trends (2005-2012) following a spatially disaggregated approach - Marivoet, Wim; De Herdt, Tom; Ulimwengu, John M. (Institute of Development Policy (IOB), University of Antwerp, 2018)
Relying on two rounds of household budget data (2005 and 2012), this paper presents a proposal for an integrated analysis of the most recent changes in welfare and poverty in the Democratic Republic of the Congo (DRC). Confronted with various methodological challenges, it proposes four ways to improve comparability of welfare and poverty across time and space. Its most salient feature is the high degree of spatial precision, which aims to capture better the variation in living conditions and economic opportunities in the DRC. Compared with the official statistics, this approach yields a completely different poverty outlook, both in terms of levels and trends. The new estimates are also triangulated with changes in undernutrition. Using the consumption indicator generated by this approach, growth at the micro level on average has been slightly positive and pro-poor for urban households, while negative and pro-rich for their rural counterparts. The combined effect of these opposing welfare trends is a minor reduction of poverty in Congolese cities and an increase in the countryside. Marked regional differences however exist, which we classify in four welfare trends. Given the differences between our analysis and the official statistics, further work is needed to check on the proposed methodology, on the robustness of the results and on the resulting poverty profile